USE OF OZONIOTHERAPY FOR SUBMENTONAL FAT REDUCTION: CASE REPORT - Maso, Adelaide; Tramontini, Luciene (Health and Society, 2023)
Ozone therapy is considered a complementary therapy that uses ozone gas as a therapeutic agent. It is a procedure that has been shown to be effective in several pathologies, and currently much explored for aesthetic dysfunctions. In recent years, the search for excellence in beauty standards, and aesthetic fashions increasingly lasting and safe is a constant. Numerous procedures are considered to reduce the double chin, but it is extremely important that the performing professional is attentive to the patient’s conditions and chooses the ideal treatment and is able to apply the appropriate technique, so that there is personal satisfaction and clinical success. With the growth in the interest of harmonization and orofacial therapy, ozone treatments have been standing out, and the same, proved to be a great lipolytic agent, reducing adiposity with few applications and without side effects. However, further studies on ozone therapy and treatment of adiposity are needed to establish optimal protocols and concentrations and frequency of ozone application in order to ensure better results for the treatment of this aesthetic dysfunction.